Unique Continuation for the Kawahara Equation - da Silva, P.N. (Trends in Computational and Applied Mathematics, 2007)
We establish a unique continuation property for the Kawahara equation. To state such property, we use a Carleman inequality for a linear differential operator related to the Kawahara equation.